Indian Governments’ Dilemma in Inclusion of Individuals with Disabilities in Organisations - Dey, Devpriya (International Journal of Psychosocial Rehabilitation, 2020)
In India only 9.7 million of 26.8 million people with disabilities (PwD) are employed (Census, 2011).Premising this, the research paper aims to present interview-based study to understand the barriers that Indian Govt. face in inclusion of individuals with disabilities in organisations. In order to comprehend the obstacles, it is essential to identify the key Govt. initiatives and the outcome of such initiatives which has been outlined from semi-structured interviews and literature. Findings indicate that the coordination among the employment exchanges with the private organisations and non-government agencies facilitating the skill development are poor, inclination of the vocational rehabilitation towards physically handicapped persons majorly, weak accessibility of the rural PwD towards vocational trainings, restricted job related information, inadequate technological skills, physical barriers at the training centers, ineffective Govt. quota system, unawareness and unwillingness of the private organisations towards incentives of hiring PwD and availability of substitute income opportunities through Govt. allowances are the major obstacles that the Govt. is facing. Findings imply that that reformation in the hiring system of PwD, awareness and reach of employment related information among the private organisations and PwD followed by the facilitation of infrastructure to the PwD is imperative to improve the employment of PwD in organisations.